![image](https://tex.z-dn.net/?f=%5Cfrac%7B3p%5E2%2Bp-2%7D%7B4-9p%5E2%7D%3D-%5Cfrac%7B%283p-2%29%28p%2B1%29%7D%7B%283p-2%29%283p%2B2%29%7D%3D-%5Cfrac%7Bp%2B1%7D%7B3p%2B2%7D+%5C%5C+-------------------+%5C%5C+%0A3p%5E2%2Bp-2%3D%3E+%5C%5C+D%3D1%5E2-4%2A3%2A%28-2%29%3D1%2B24%3D25%3D5%5E2+%5C%5C+p1%3D%28-1%2B5%29%2F6%3D4%2F6%3D2%2F3+%5C%5C+p2%3D%28-1-5%29%2F6%3D-6%2F6%3D-1+%5C%5C+%3D%3E+%28p-2%2F3%29%28p%2B1%29%3D%283p-2%29%28p%2B1%29+%5C%5C+------------------------+%5C%5C+%0A4-9p%5E2%3D-9p%5E2%2B4%3D-%289p%5E2-4%29%3D-%283p-2%29%283p%2B2%29)
\\ D=1^2-4*3*(-2)=1+24=25=5^2 \\ p1=(-1+5)/6=4/6=2/3 \\ p2=(-1-5)/6=-6/6=-1 \\ => (p-2/3)(p+1)=(3p-2)(p+1) \\ ------------------------ \\
4-9p^2=-9p^2+4=-(9p^2-4)=-(3p-2)(3p+2)" alt="\frac{3p^2+p-2}{4-9p^2}=-\frac{(3p-2)(p+1)}{(3p-2)(3p+2)}=-\frac{p+1}{3p+2} \\ ------------------- \\
3p^2+p-2=> \\ D=1^2-4*3*(-2)=1+24=25=5^2 \\ p1=(-1+5)/6=4/6=2/3 \\ p2=(-1-5)/6=-6/6=-1 \\ => (p-2/3)(p+1)=(3p-2)(p+1) \\ ------------------------ \\
4-9p^2=-9p^2+4=-(9p^2-4)=-(3p-2)(3p+2)" align="absmiddle" class="latex-formula">